Making the Move: Empowering Student Teachers as Teacher Researchers. Issue 3 (2nd July 2020) - Dassa, Lori; Nichols, Bryan
Abstract: This paper describes the development, implementation, and follow up study of a program for undergraduate research in education, student teachers as action researchers (STAR). Students in a new urban education honors program at a large public university were given coursework in action research, developed a research plan in their practicums, implemented it during their student teaching, and presented the results at an undergraduate research conference. After examining student projects, faculty experiences, and follow-up interviews with the participants, we found that while there are challenges, the STAR program provides a useful introduction to teacher action research that empowers new teachers, giving them confidence and an early desire to use data to improve their instruction and benefit their students. We conclude with implications for modern classrooms and insights into expansion or adaptation of the technique for interested teacher educators.